Adaptation of The Ukrainian Version of The Combat Exposure Scale (CES-UA) - Kasiianenko, Daria (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2025)
Objective. The objective of this study was to adapt the original Combat Exposure Scale (CES; Keane et al., 1989) into the Ukrainian language, translated as the Combat Exposure Scale–Ukrainian version (CES-UA), for use in psychological practice with active-duty service members, veterans, and individuals with combat experience. This scale is a widely used self-report tool for assessing combat-related situations. Despite its international value, a validated Ukrainian version was lacking. Given the urgent psychological needs of military personnel amid Russia’s full-scale invasion of Ukraine, this gap required immediate attention. Methods. The CES was translated and culturally adapted into Ukrainian using a forward–backward method involving a professional translator, bilingual veterans, and university faculty. Psychometric testing included 513 male service members (436 online, 77 paper). Data analysis was conducted in R (R Core Team, 2024) and RStudio (Posit, 2024). Results. Confirmatory factor analysis confirmed the unidimensional structure of the Ukrainian version of the Combat Exposure Scale (CES-UA). Most fit indices demonstrated an excellent level of correspondence between the theoretical model and the empirical data (CFI = 0.999, TLI = 0.998, SRMR = 0.034). Subsequent evaluation of the model confirmed its key psychometric characteristics. As a result, multiple statistical methods confirmed that the CES-UA demonstrates high reliability (α = 0.91, ordinal α = 0.95, ω = 0.93, CR = 0.94), supported convergent validity (AVE = 0.729), discriminant validity (HTMT = 0.046), and measurement invariance across age groups. Conclusion. The Ukrainian version of the Combat Exposure Scale (CES-UA) is a reliable and valid instrument and is recommended for use with Ukrainian-speaking military personnel and veterans in both clinical practice and scientific research.